The Effects of Social Media Use and School Culture on Students Learning Outcomes Junior High School 01 of Kisam Ilir Sub-District - Yanto, Hiri; Arafat, Yassir; Yan, Alhadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research is motivated by conditions among teachers. frequently use social media. The research objective was to determine the effect of using social media and school culture on student learning outcomes at Junior High School 01 Kisam Ilir, Muaradua Kisam District. This research uses quantitative methods. The population is 172 people and the research sample is 90 respondents. Data collection uses questionnaires and documentation of student learning outcomes which are then tested using the SPSS version 2.5 program. Hypothesis testing at the 5% significance level using the t-test, the conclusion of this study H1 is rejected, this shows that there is no influence between variable X1 on variable Y. For H2 is accepted, it shows that there is an influence between variable X2 and variable Y by 97%. To test the effect of variables X1 and X2 on Y simultaneously, the F test is used which results in H3 are rejected. The implication of this research is to cultivate social media in the school environment to support learning achievement